Screening of parameters for hydrolysis of sugarcane bagasse with Aspergillus niger for Microcrystalline Cellulose (MCC) production - Jimat, Dzun Noraini; Salleh, Norhidayah; Avicenna, Avicenna (2015)
Background: Microcrystalline cellulose (MCC) can be made from any lignocellulose materials with high cellulose content such as sugarcane bagasse (SCB). MCC is widely used in industries as emulsifier, stabilizer, anti-caking agent and as tablet excipient. Conventional methods to produce MCC such as acid hydrolysis and mechanical treatment posed significant drawbacks; large amount of acid is required and increased defibrillation of alpha cellulose, respectively. The utilization of sugarcane bagasse for MCC production could help to reduce the problem of lignocellulosic waste. The aim of this study was to treat the sugarcane bagasse using fungal cellulases hydrolysis as a pretreatment method thus assisting the fibrillation of fiber cellulose via ultrasonication. Methods: The sugarcane bagasse were treated using fungal cellulases hydrolysis as a pretreatment method and the fibrillation of fiber cellulose using ultrasonication. The effects of solid-state fermentation of Aspergillus niger on cellulases activities and morphological changes of sugarcane bagasse were investigated. Variables such as sugarcane bagasse particle size (400 and 600 µm), inoculum size (2% and 5%), medium pH (5 and 7), and fermentation time (5 and 15 days) were screened using 2-level factorial design (Design expert software, Stat-Ease Inc., Version 8.0) Results: Analysis of variance (ANOVA) showed that the most significant parameter that affected the structural changes of sugarcane bagasse was its particle size. The increased glucose production indicated the increased defibrillation of sugarcane bagasse. Conclusion: The use of fungal pretreatment through solid state fermentation of Aspergillus niger prior to ultrasonication was found to assist the later process in isolating MCC. The results obtained from enzyme assays, optical microscope, SEM and FTIR showed the supporting evidence about the successful extraction of MCC from SCB.